2017
DOI: 10.1007/s10549-017-4152-5
|View full text |Cite
|
Sign up to set email alerts
|

Plasma carotenoids and the risk of premalignant breast disease in women aged 50 and younger: a nested case–control study

Abstract: Purpose To examine the association of plasma carotenoids, micronutrients in fruits and vegetables, with risk of premalignant breast disease (PBD) in younger women. Methods Blood samples were collected at the Siteman Cancer Center between 2008 and 2012 from 3,537 women aged 50 or younger with no history of cancer or PBD. The analysis included 147 participants diagnosed with benign breast disease or breast carcinoma in situ during a 27-month followup and 293 controls. Cases and controls were matched on age, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Carotenoids may play a role in BC early development. The relative levels of the different types of carotenoids are important to take into account as well as a potential influence from other lifestyle factors 58 .…”
Section: Carotenoidsmentioning
confidence: 99%
“…Carotenoids may play a role in BC early development. The relative levels of the different types of carotenoids are important to take into account as well as a potential influence from other lifestyle factors 58 .…”
Section: Carotenoidsmentioning
confidence: 99%
“…Plasma samples from the cohort have been evaluated for carotenoid concentrations and risk of proliferative benign breast disease diagnosed from baseline through April 2016 [ 22 ]. Among women under age 50 we observed that African Americans had lower levels of alpha and beta-carotene and higher levels of beta-cryptoxanthin and lutein/zeaxanthin.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies demonstrated inverse associations between the concentration of retinol and carotenoids and the risk of breast cancer in pre- or post-menopausal women [ 47 , 48 , 49 , 50 , 51 , 52 , 112 , 113 , 114 , 115 , 116 ], even though not all of them were statistically significant ( Table 1 ) [ 52 , 113 , 114 , 116 , 117 , 118 ]. In particular, high serum or plasma concentrations of α- and β-carotene mostly exhibited a significantly reduced risk of invasive breast cancer, up to a 60–70% reduction in risk [ 47 , 48 , 49 , 50 , 51 , 52 , 112 ].…”
Section: Associations Of Vitamin a And Carotenoids With Breast Cancer Risk In Epidemiological Studiesmentioning
confidence: 99%
“…In particular, high serum or plasma concentrations of α- and β-carotene mostly exhibited a significantly reduced risk of invasive breast cancer, up to a 60–70% reduction in risk [ 47 , 48 , 49 , 50 , 51 , 52 , 112 ]. High levels of plasma carotenoids have also been found to be inversely associated with lower risks of overall cancer, as well as premalignant breast diseases such as benign breast disease or breast cancer in situ [ 113 , 118 ]. In addition, survival rates, recurrence risks, and other parameters of breast cancer were related with levels of retinol and carotenoids levels.…”
Section: Associations Of Vitamin a And Carotenoids With Breast Cancer Risk In Epidemiological Studiesmentioning
confidence: 99%